Magnetic charge propagation upon a 3D artificial spin-ice - A. May (Nature Portfolio, 2021)
Two-dimensional artificial spin-ice systems have been studied for over 15 years but do not capture the detailed geometry of their bulk counterparts. Here, the authors fabricate a three-dimensional artificial spin-ice and show that the surface termination plays a crucial role in dictating the magnetic charge transport.